Helicobacter pylori does not play a part in the dyspeptic complaints of rheumatology patients receiving long term treatment with non-steroidal anti-inflammatory drugs. Issue 7 (1st July 2002) - Calvet, X; Gratacòs, J; Font, J; Larrosa, M; Sanfeliu, I; Roqué, M
Abstract : Background: The presence of dyspeptic symptoms is a common finding in patients treated with non-steroidal anti-inflammatory drugs (NSAIDs). Some studies seem to support the involvement of Helicobacter pylori infection in the dyspeptic symptoms reported by these patients, and suggest that eradication may be useful. Objective: To determine the variables related to dyspepsia in rheumatology patients requiring NSAID treatment, assessing in particular the role of Helicobacter pylori infection. Methods: One hundred and eighty six consecutive patients with a rheumatological disorder requiring NSAID treatment (68 male, 118 female; mean (SD) age 55 (15) years) were included in a cross sectional study; dyspeptic symptoms were measured by a previously validated scale. Helicobacter pylori infection was determined by serology. Variables related to the severity of symptoms and the need for antisecretory drugs were determined by multivariate analysis. Results: No relation was found between Helicobacter pylori infection and dyspepsia or any of its surrogate markers (antisecretory drug use or NSAID intolerance). Female sex and treatment with antisecretory drugs were found to be independent predictors for the appearance and severity of dyspeptic symptoms. The only independent predictive variables of the requirement for antisecretory drugs were age, previous ulcer disease, taking NSAIDs with a medium or high anti-inflammatory potential, and the symptoms score. Conclusion: Helicobacter pylori infection does not seem to play any part in the gastric symptoms of patients treated long term with NSAIDs.